Degradable disposable tableware and preparation method thereof

By hot-pressing the bamboo fiber, chitosan and other materials, degradable disposable tableware with good degradation rate, stretching effect and self-cleaning performance is prepared, which solves the shortcomings of existing tableware in these aspects and reduces environmental pollution.

CN119505562APending Publication Date: 2025-02-25GUANGZHOU XINXINFA TABLEWARE SUPPLIES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411845149.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing biodegradable tableware has shortcomings in terms of stretching effect and self-cleaning effect, and traditional tableware materials are not easy to degrade, polluting the environment.

Method used

Materials such as bamboo fiber, chitosan, nanosilica, polyvinyl alcohol, gum arabic, rice husk powder, epoxy group modified silanes and modified carbon nanotubes are prepared by stirring, mixing and hot pressing molding.

Benefits of technology

It improves the degradation rate, stretching effect and self-cleaning performance of tableware, ensures that tableware can be effectively degraded after use, reduces environmental pollution, and has good mechanical properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses degradable disposable tableware and a preparation method thereof.The preparation method includes the steps that bamboo fibers, chitosan, nano-silicon dioxide, polyvinyl alcohol, Arabic gum, rice hull powder, epoxy group modified silane, modified carbon nanotubes and water are stirred and mixed to obtain mixed slurry, the mixed slurry is injected into a mold, and the degradable disposable tableware is obtained. And after hot pressing and molding, demolding, taking down and drying a demolded finished product, trimming, deburring and disinfecting to obtain the degradable disposable tableware. Polylactic acid and siloxane groups in the tableware have a good self-cleaning effect, the self-cleaning performance of the tableware is improved when the tableware is applied to the tableware, meanwhile, after carboxyl polylactic acid reacts with hydroxylated silane, the substitution degree of polylactic acid is improved, the self-cleaning effect of polylactic acid is further improved, and the disposable tableware also has a good degradation rate and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a degradable disposable tableware and a preparation method thereof. Background Art

[0002] Tableware is an indispensable daily necessity for people. Traditional fast food tableware is made of organic plastic materials, which are not easy to degrade after use. Burning will pollute the environment and is harmful to human health. In addition, traditional tableware has poor mechanical properties and is easily damaged. During long-term storage, there will be pollutants on the surface, which will affect its normal use. Therefore, how to avoid these phenomena is the key to solving the problem. For example, patent CN117050491A discloses a degradable tableware and a preparation method thereof. This invention belongs to the technical field of degradable tableware, and specifically provides degradable tableware that is easy to degrade as a whole, and has excellent waterproof and oil-proof properties and mechanical properties. However, its stretching effect and self-cleaning effect are not improved. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] In view of the deficiencies in the prior art, the present invention provides a degradable disposable tableware and a preparation method thereof, which has a good degradation rate as well as good self-cleaning effect and stretching effect.

[0005] (II) Technical solution

[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a degradable disposable tableware, comprising the following components by weight: 10-14 parts by weight of bamboo fiber, 5-7 parts by weight of chitosan, 1-1.5 parts by weight of nano-silicon dioxide, 5-10 parts by weight of polyvinyl alcohol, 4-8 parts by weight of gum arabic, 15-25 parts by weight of rice husk powder, 4-10 parts by weight of epoxy group modified silane, 3-6 parts by weight of modified carbon nanotubes, and 4-6 parts by weight of water.

[0007] Preferably, the preparation method of the epoxy group modified silane is:

[0008] (1) adding vinyl trichlorosilane and diethanolamine to tetrahydrofuran solvent, introducing nitrogen protection, and continuously adding triethylamine catalyst thereto, stirring and reflux at 65-80° C. for 3-6 hours, and after the reaction is completed, removing the solvent by distillation under reduced pressure, washing and drying to obtain hydroxylated silane;

[0009] (2) dissolving polylactic acid in tetrahydrofuran, then adding phthalic anhydride and stannous octoate catalyst, reacting in a hydrothermal reactor at 85-110° C. for 3-5 hours, removing the solvent after the reaction, washing the product, and obtaining carboxyl polylactic acid;

[0010] (3) adding carboxyl polylactic acid and hydroxylated silane into a reactor containing N,N-dimethylformamide, stirring and mixing, continuing to add p-toluenesulfonic acid catalyst, heating to 90-120° C. for reaction for 7-12 hours, and then rotary distilling, washing with deionized water, and drying to obtain polylactic acid modified olefinic silane;

[0011] (4) Adding polylactic acid modified olefinic silane to toluene solvent, stirring evenly, then adding aqueous hydrogen peroxide solution, stirring and reacting at 20-30° C. for 3-7 hours. After the reaction is completed, standing, extracting, taking the organic phase for drying, and distilling under reduced pressure to obtain epoxy group modified silane.

[0012] Preferably, the mass ratio of vinyltrichlorosilane, diethanolamine and triethylamine catalyst in (1) is 1:2.1-2.4:0.02-0.03.

[0013] Preferably, the mass ratio of polylactic acid, phthalic anhydride and stannous octoate catalyst in (2) is 1:0.2-0.4:0.01-0.03.

[0014] Preferably, the mass ratio of carboxyl polylactic acid, hydroxylated silane and p-toluenesulfonic acid catalyst in (3) is 1.2-1.8:1:0.02-0.04.

[0015] Preferably, the mass ratio of the polylactic acid modified olefinic silane to the hydrogen peroxide aqueous solution in (4) is 1:2.1-2.5.

[0016] Preferably, the preparation method of the modified carbon nanotubes is: 2-3 parts by weight of sodium dodecyl sulfate emulsifier and 3-7 parts by weight of vinyl carbon nanotubes are added to deionized water, and after uniform dispersion, 4-10 parts by weight of polylactic acid modified olefinic silane, 5-9 parts by weight of acryl alcohol, and 6-8 parts by weight of allyltrimethylammonium chloride are added, nitrogen is introduced for protection, and then 0.8-1 parts by weight of azobisisobutyronitrile initiator is added, reacting at 70-90° C. for 4-6 hours, washing with deionized water and ethanol in turn, and drying to obtain modified carbon nanotubes.

[0017] Preferably, the preparation method of the degradable disposable tableware is: bamboo fiber, chitosan, nano-silica, polyvinyl alcohol, gum arabic, rice husk powder, epoxy group-modified silane, modified carbon nanotubes, and water are stirred and mixed at 350-500 rpm for 12-20 min to obtain a mixed slurry, the mixed slurry is injected into a mold, hot-pressed at a temperature of 160-175°C and a pressure of 120-140 MPa for 15-30 min, and after molding, demolded, the demolded finished product is taken out and dried at 70-90°C for 10-20 min, trimmed, deburred, and disinfected to obtain degradable disposable tableware.

[0018] (III) Beneficial technical effects

[0019] The present invention prepares a mixed slurry by stirring and mixing bamboo fiber, chitosan, nano silicon dioxide, polyvinyl alcohol, gum arabic, rice husk powder, epoxy group-modified silane, modified carbon nanotubes and water, injecting the mixed slurry into a mold, hot pressing, and demolding after molding, removing the demolded finished product, drying it, trimming and removing burrs, and disinfecting it to obtain degradable disposable tableware.

[0020] During the hot pressing process, the epoxy groups in the epoxy-modified silane will undergo a ring-opening reaction with the hydroxyl groups in the modified carbon nanotubes and chitosan, forming a cross-linked network between each other, making them more tightly connected and increasing the mechanical properties of the tableware; the polylactic acid and siloxane groups in the tableware have good self-cleaning effects, and their application in the tableware improves their self-cleaning properties. At the same time, after the carboxyl polylactic acid and hydroxylated silane react, the substitution degree of the polylactic acid is increased, further improving its self-cleaning effect; the carbon nanotubes themselves have good mechanical and self-cleaning properties, and the disposable tableware of the present invention also has a good degradation rate. DETAILED DESCRIPTION

[0021] The preparation process of vinyl carbon nanotubes refers to the journal "Materials Science and Engineering Plastics" Volume 23, Issue 4, "Surface Vinyl Functionalization of Multi-walled Carbon Nanotubes": 0.3g of multi-walled carbon nanotubes were added to 30mL of 98% concentrated sulfuric acid and 10mL of 70% concentrated nitric acid, refluxed at 140°C for 1h, filtered, and washed. 0.1g of the acidified carbon nanotubes obtained were weighed and dispersed in 15mL of acetone and 15mL of chloroform, 2mL of triethylamine and 5mL of acryloyl chloride were added, and the reaction was carried out at 40°C for 24h. Then 10mL of ethanol was added and stirred for 2h, filtered, and washed to obtain vinyl carbon nanotubes.

[0022] Example 1

[0023] (1) adding vinyl trichlorosilane and diethanolamine to tetrahydrofuran solvent, introducing nitrogen protection, and continuously adding triethylamine catalyst, wherein the mass ratio of vinyl trichlorosilane, diethanolamine, and triethylamine catalyst is 1:2.1:0.02, stirring and refluxing at 65° C. for 3 h, and after the reaction is completed, removing the solvent by distillation under reduced pressure, washing, and drying to obtain hydroxylated silane;

[0024] (2) dissolving polylactic acid in tetrahydrofuran, then adding phthalic anhydride and stannous octoate catalyst, wherein the mass ratio of polylactic acid, phthalic anhydride and stannous octoate catalyst is 1:0.2:0.01, reacting in a hydrothermal reactor at 85° C. for 3 hours, removing the solvent after the reaction, washing the product, and obtaining carboxyl polylactic acid;

[0025] (3) adding carboxylated polylactic acid and hydroxylated silane to a reactor containing N,N-dimethylformamide, stirring and mixing, and continuing to add p-toluenesulfonic acid catalyst, wherein the mass ratio of carboxylated polylactic acid, hydroxylated silane, and p-toluenesulfonic acid catalyst is 1.2:1:0.02, heating to 90° C. for reaction for 7 h, and then performing rotary distillation after completion, washing with deionized water, and drying to obtain polylactic acid modified olefinic silane;

[0026] (4) adding polylactic acid modified olefinic silane to a toluene solvent, stirring evenly, and then adding an aqueous hydrogen peroxide solution thereto, wherein the mass ratio of polylactic acid modified olefinic silane to the aqueous hydrogen peroxide solution is 1:2.1, stirring and reacting at 20° C. for 3 h. After the reaction is completed, standing, extracting, taking the organic phase for drying, and distilling under reduced pressure to obtain epoxy group modified silane;

[0027] (5) adding 2 parts by weight of sodium dodecyl sulfate emulsifier and 3 parts by weight of vinyl carbon nanotubes to deionized water, and adding 4 parts by weight of polylactic acid modified vinyl silane, 5 parts by weight of acryl alcohol, and 6 parts by weight of allyltrimethylammonium chloride after uniform dispersion, and then introducing nitrogen protection, and then continuing to add 0.8 parts by weight of azobisisobutyronitrile initiator, reacting at 70° C. for 4 hours, washing with deionized water and ethanol in turn, and drying to obtain modified carbon nanotubes;

[0028] (6) 10 parts by weight of bamboo fiber, 5 parts by weight of chitosan, 1 part by weight of nano-silica, 5 parts by weight of polyvinyl alcohol, 4 parts by weight of gum arabic, 15 parts by weight of rice husk powder, 4 parts by weight of epoxy group-modified silane, 3 parts by weight of modified carbon nanotubes, and 4 parts by weight of water are stirred and mixed at 350 rpm for 12 minutes to obtain a mixed slurry, which is injected into a mold and hot-pressed at a temperature of 160° C. and a pressure of 120 MPa for 15 minutes. After molding, the mold is removed, and the finished product after demolding is taken out and dried at 70° C. for 10 minutes, trimmed and deburred, and sterilized to obtain degradable disposable tableware.

[0029] Example 2

[0030] (1) adding vinyl trichlorosilane and diethanolamine to tetrahydrofuran solvent, introducing nitrogen protection, and continuously adding triethylamine catalyst, wherein the mass ratio of vinyl trichlorosilane, diethanolamine, and triethylamine catalyst is 1:2.4:0.03, stirring and refluxing at 80° C. for 6 h, and after the reaction is completed, removing the solvent by distillation under reduced pressure, washing, and drying to obtain hydroxylated silane;

[0031] (2) dissolving polylactic acid in tetrahydrofuran, then adding phthalic anhydride and stannous octoate catalyst, wherein the mass ratio of polylactic acid, phthalic anhydride and stannous octoate catalyst is 1:0.4:0.03, reacting in a hydrothermal reactor at 110° C. for 5 hours, removing the solvent after the reaction, washing the product, and obtaining carboxyl polylactic acid;

[0032] (3) adding carboxylated polylactic acid and hydroxylated silane to a reactor containing N,N-dimethylformamide, stirring and mixing, and continuing to add p-toluenesulfonic acid catalyst, wherein the mass ratio of carboxylated polylactic acid, hydroxylated silane, and p-toluenesulfonic acid catalyst is 1.8:1:0.04, heating to 120° C. for reaction for 12 h, and then performing rotary distillation, washing with deionized water, and drying to obtain polylactic acid modified olefinic silane;

[0033] (4) adding polylactic acid modified olefinic silane to a toluene solvent, stirring evenly, and then adding an aqueous hydrogen peroxide solution, wherein the mass ratio of polylactic acid modified olefinic silane to the aqueous hydrogen peroxide solution is 1:2.5, stirring and reacting at 30° C. for 7 h. After the reaction is completed, standing, extracting, taking the organic phase for drying, and distilling under reduced pressure to obtain epoxy group modified silane;

[0034] (5) adding 3 parts by weight of sodium dodecyl sulfate emulsifier and 7 parts by weight of vinyl carbon nanotubes to deionized water, and adding 10 parts by weight of polylactic acid modified vinyl silane, 9 parts by weight of acryl alcohol, and 8 parts by weight of allyltrimethylammonium chloride after uniform dispersion, and then introducing nitrogen protection, and then continuing to add 1 part by weight of azobisisobutyronitrile initiator, reacting at 90° C. for 6 hours, washing with deionized water and ethanol in turn, and drying to obtain modified carbon nanotubes;

[0035] (6) 14 parts by weight of bamboo fiber, 7 parts by weight of chitosan, 1.5 parts by weight of nano-silica, 10 parts by weight of polyvinyl alcohol, 8 parts by weight of gum arabic, 25 parts by weight of rice husk powder, 10 parts by weight of epoxy group-modified silane, 6 parts by weight of modified carbon nanotubes, and 6 parts by weight of water were stirred and mixed at 500 rpm for 20 min to obtain a mixed slurry, which was injected into a mold and hot-pressed at a temperature of 175° C. and a pressure of 140 MPa for 30 min. After molding, the mold was removed, and the finished product after demolding was taken out and dried at 90° C. for 20 min, trimmed and deburred, and sterilized to obtain biodegradable disposable tableware.

[0036] Example 3

[0037] (1) adding vinyl trichlorosilane and diethanolamine to tetrahydrofuran solvent, introducing nitrogen protection, and continuously adding triethylamine catalyst, wherein the mass ratio of vinyl trichlorosilane, diethanolamine, and triethylamine catalyst is 1:2.25:0.025, stirring and refluxing at 75° C. for 4 h, and after the reaction is completed, removing the solvent by distillation under reduced pressure, washing, and drying to obtain hydroxylated silane;

[0038] (2) dissolving polylactic acid in tetrahydrofuran, then adding phthalic anhydride and stannous octoate catalyst, wherein the mass ratio of polylactic acid, phthalic anhydride and stannous octoate catalyst is 1:0.3:0.02, reacting in a hydrothermal reactor at 95° C. for 4 hours, removing the solvent after the reaction, washing the product, and obtaining carboxyl polylactic acid;

[0039] (3) adding carboxyl polylactic acid and hydroxylated silane to a reactor containing N,N-dimethylformamide, stirring and mixing, and continuing to add p-toluenesulfonic acid catalyst, wherein the mass ratio of carboxyl polylactic acid, hydroxylated silane, and p-toluenesulfonic acid catalyst is 1.6:1:0.03, heating to 105° C. for 10 h, and then performing rotary distillation, washing with deionized water, and drying to obtain polylactic acid modified olefinic silane;

[0040] (4) adding polylactic acid modified olefinic silane to a toluene solvent, stirring evenly, and then adding an aqueous hydrogen peroxide solution thereto, wherein the mass ratio of the polylactic acid modified olefinic silane to the aqueous hydrogen peroxide solution is 1:2.3, stirring and reacting at 25° C. for 5 h. After the reaction is completed, standing, extracting, taking the organic phase for drying, and distilling under reduced pressure to obtain epoxy group modified silane;

[0041] (5) adding 2.5 parts by weight of sodium dodecyl sulfate emulsifier and 5 parts by weight of vinyl carbon nanotubes into deionized water, and adding 7 parts by weight of polylactic acid modified vinyl silane, 6 parts by weight of acryl alcohol, and 7 parts by weight of allyltrimethylammonium chloride after uniform dispersion, and then introducing nitrogen protection, and then continuing to add 0.9 parts by weight of azobisisobutyronitrile initiator, reacting at 80° C. for 5 hours, washing with deionized water and ethanol in turn, and drying to obtain modified carbon nanotubes;

[0042] (6) 12 parts by weight of bamboo fiber, 6 parts by weight of chitosan, 1.25 parts by weight of nano-silicon dioxide, 7.5 parts by weight of polyvinyl alcohol, 6 parts by weight of gum arabic, 20 parts by weight of rice husk powder, 7 parts by weight of epoxy group-modified silane, 4.5 parts by weight of modified carbon nanotubes, and 5 parts by weight of water were stirred and mixed, and stirred at 450 rpm for 16 minutes to obtain a mixed slurry, and the mixed slurry was injected into a mold, and hot-pressed at a temperature of 170° C. and a pressure of 130 MPa for 22 minutes. After molding, the mold was removed, and the demolded product was taken out and dried at 80° C. for 15 minutes, trimmed, deburred, and sterilized to obtain degradable disposable tableware.

[0043] Comparative Example 1

[0044] The difference between this comparative example and Example 3 is that no epoxy group-modified silane is added.

[0045] Comparative Example 2

[0046] The difference between this comparative example and Example 3 is that no modified carbon nanotubes are added.

[0047] Performance Testing

[0048] Degradation performance test: with reference to the national standard GB / T19277.1-2011 "Determination of the ultimate aerobic biodegradability of materials under controlled composting conditions by measuring the released carbon dioxide method Part 1: General method", the degradation performance test was carried out on the degradable disposable tableware prepared in Examples 1-3 and Comparative Examples 1-2, respectively. Test conditions: the degradable disposable tableware prepared in Examples 1-3 and Comparative Examples 1-2 were mixed with inocula as test samples, and the test samples were placed in a composting container. The water content of the test samples was 50%, and the volume placed was no more than 3 / 4 of the composting container. The composting container containing the test samples was placed in an experimental environment of 58°C. After 45 days, the amount of carbon dioxide released by the material was measured. Three groups of parallel samples were tested and the average value was taken. Mechanical properties test: refer to the national standard GB / T1040.2-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics" method for testing; the test specimen is 1A type dumbbell type, thickness 4mm, before the test, the sample is kept at a constant temperature of 23 ° C and relative humidity of 50% for 24 hours, 5 parallel groups are tested, and the average value is taken. The results are shown in Table 1.

[0049] Table 1: Degradation rate and tensile properties tested.

[0050] project Degradation rate (%) Tensile strength(Mpa) Example 1 61.5 71.3 Example 2 62.7 73.9 Example 3 66.4 71.6 Comparative Example 1 71.6 62.3 Comparative Example 2 73.4 61.7

[0051] It can be seen from Table 1 that Examples 1-3 and Comparative Examples 1-2 of the present invention have better degradation effects, and Examples 1-3 and Comparative Examples 1-2 have better stretching effects.

[0052] The surface wettability of the samples of Examples 1-5 and Comparative Examples 1-2 was characterized according to JC2000D, and the contact angle test was performed.

[0053] Table 2: Contact angle test.

[0054] project Contact Angle Example 1 124.8° Example 2 125.6° Example 3 121.4° Comparative Example 1 83.1° Comparative Example 2 82.5°

[0055] As can be seen from Table 2, compared with Comparative Examples 1-2, the contact angles of Examples 1-3 are larger, resulting in the water droplets being unable to spread and being very easy to slide, indicating that the degradable disposable tableware prepared by the present invention has a good self-cleaning function.

[0056] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A degradable disposable tableware, characterized in that: The invention comprises the following components by weight: 10-14 parts by weight of bamboo fiber, 5-7 parts by weight of chitosan, 1-1.5 parts by weight of nano silicon dioxide, 5-10 parts by weight of polyvinyl alcohol, 4-8 parts by weight of gum arabic, 15-25 parts by weight of rice husk powder, 4-10 parts by weight of epoxy group modified silane, 3-6 parts by weight of modified carbon nanotubes and 4-6 parts by weight of water.

2. The degradable disposable tableware according to claim 1, characterized in that: The preparation method of the epoxy group modified silane is: (1) adding vinyl trichlorosilane and diethanolamine to tetrahydrofuran solvent, introducing nitrogen protection, and continuously adding triethylamine catalyst thereto, stirring and reflux at 65-80° C. for 3-6 hours, and after the reaction is completed, removing the solvent by distillation under reduced pressure, washing and drying to obtain hydroxylated silane; (2) dissolving polylactic acid in tetrahydrofuran, then adding phthalic anhydride and stannous octoate catalyst, reacting in a hydrothermal reactor at 85-110° C. for 3-5 hours, removing the solvent after the reaction, washing the product, and obtaining carboxyl polylactic acid; (3) adding carboxyl polylactic acid and hydroxylated silane into a reactor containing N,N-dimethylformamide, stirring and mixing, continuing to add p-toluenesulfonic acid catalyst, heating to 90-120° C. for reaction for 7-12 hours, and then rotary distilling, washing with deionized water, and drying to obtain polylactic acid modified olefinic silane; (4) Adding polylactic acid modified olefinic silane to toluene solvent, stirring evenly, then adding aqueous hydrogen peroxide solution, stirring and reacting at 20-30° C. for 3-7 hours. After the reaction is completed, standing, extracting, taking the organic phase for drying, and distilling under reduced pressure to obtain epoxy group modified silane.

3. The degradable disposable tableware according to claim 2, characterized in that: The mass ratio of vinyltrichlorosilane, diethanolamine and triethylamine catalyst in (1) is 1:2.1-2.4:0.02-0.

03.

4. The degradable disposable tableware according to claim 2, characterized in that: The mass ratio of polylactic acid, phthalic anhydride and stannous octoate catalyst in (2) is 1:0.2-0.4:0.01-0.

03.

5. The degradable disposable tableware according to claim 2, characterized in that: The mass ratio of carboxyl polylactic acid, hydroxylated silane and p-toluenesulfonic acid catalyst in (3) is 1.2-1.8:1:0.02-0.

04.

6. The degradable disposable tableware according to claim 2, characterized in that: The mass ratio of the polylactic acid modified olefinic silane to the hydrogen peroxide aqueous solution in (4) is 1:2.1-2.

5.

7. The degradable disposable tableware according to claim 1, characterized in that: The preparation method of the modified carbon nanotubes is as follows: 2-3 parts by weight of sodium dodecyl sulfate emulsifier and 3-7 parts by weight of vinyl carbon nanotubes are added to deionized water, and after uniform dispersion, 4-10 parts by weight of polylactic acid modified olefinic silane, 5-9 parts by weight of acryl alcohol, and 6-8 parts by weight of allyltrimethylammonium chloride are added, nitrogen is introduced for protection, and then 0.8-1 parts by weight of azobisisobutyronitrile initiator is continuously added, reacting at 70-90° C. for 4-6 hours, washing with deionized water and ethanol in turn, and drying to obtain the modified carbon nanotubes.

8. A method for preparing the degradable disposable tableware according to any one of claims 1 to 7, characterized in that: The preparation method of the degradable disposable tableware comprises the following steps: mixing bamboo fiber, chitosan, nano-silicon dioxide, polyvinyl alcohol, gum arabic, rice husk powder, epoxy group-modified silane, modified carbon nanotubes and water, stirring at 350-500 rpm for 12-20 minutes to obtain a mixed slurry, injecting the mixed slurry into a mold, hot pressing at a temperature of 160-175° C. and a pressure of 120-140 MPa for 15-30 minutes, demolding after molding, taking out the demolded finished product, drying it at 70-90° C. for 10-20 minutes, trimming and removing burrs, and sterilizing it to obtain the degradable disposable tableware.